2020
DOI: 10.1016/j.ejvs.2019.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Low Risk of Procedure Related Major Amputation Following Revascularisation for Intermittent Claudication: A Population Based Study

Abstract: WHAT THIS PAPER ADDSThe procedure-related amputation rate is insufficiently investigated. Revascularization for intermittent claudication confers a low but existing risk of procedure related major amputation within the first post-procedural year.Objective: To investigate the risk of procedure-related major amputation attributable to revascularization for intermittent claudication (IC) in a population-based observational cohort study. Methods: All patients who underwent open or endovascular lower limb revascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…However, historical data illustrate that the risk of amputation in patients with IC remains quite low 2 . A recent, population-based study estimated yearly risk of major amputation at 0.2%, consistent with the estimates in our study 34 . Although revascularization, either by endovascular or surgical means, can improve IC symptoms, suboptimal technical outcomes, and intervention failure can lead to reinterventions and clinical deterioration, negatively altering the clinical course of IC 15 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, historical data illustrate that the risk of amputation in patients with IC remains quite low 2 . A recent, population-based study estimated yearly risk of major amputation at 0.2%, consistent with the estimates in our study 34 . Although revascularization, either by endovascular or surgical means, can improve IC symptoms, suboptimal technical outcomes, and intervention failure can lead to reinterventions and clinical deterioration, negatively altering the clinical course of IC 15 .…”
Section: Discussionsupporting
confidence: 88%
“…2 A recent, populationbased study estimated yearly risk of major amputation at 0.2%, consistent with the estimates in our study. 34 Although revascularization, either by endovascular or surgical means, can improve IC symptoms, suboptimal technical outcomes, and intervention failure can lead to reinterventions and clinical deterioration, negatively altering the clinical course of IC. 15 Indeed, the current meta-analysis confirmed significantly more revascularizations are performed once invasive treatments are initiated.…”
Section: Discussionmentioning
confidence: 99%
“…21 Swedvasc has not yet been validated for procedures related to PAD, but Djerf et al found that almost half of patients registered in Swedvasc due to major amputation following intermittent claudication in fact had CLTI. 38 Therefore, the risk of misclassification of CLTI as intermittent claudication was probably low in the present study. It cannot be ruled out, however, that some patients were reclassified as having CLTI if the surgery for intermittent claudication failed.…”
Section: Study Strengths and Limitationsmentioning
confidence: 58%
“…It would also have been desirable to analyse precise location and extent of the atherosclerotic lesions according to the Trans-Atlantic Inter-Society Consensus II classification, 30 as previous studies have implicated a correlation between lesion extent and risk of amputation. 10 Due to the risk of misclassification of CLTI as IC 31 and uncertainty of amputation data in patient registries, the reported association between diabetes and increased risk of major amputation should be interpreted very cautiously. Unfortunately, we did not have ethical permission to validate amputation data in individual patient files at different centres.…”
Section: Discussionmentioning
confidence: 99%